The mediating and moderating effects on the relationship between job satisfaction and job performance: Organizational commitment and employee empowerment as mediator and Islamic culture as moderator - Al Qahtani MNahi, Mutlaq M (2018)
The main objective of this study is to examine the mediating role of organizational commitment and employees’ empowerment as well as the moderating role of Islamic culture on the relationship between job satisfaction and job performance of academicians in public universities in the Kingdom of Saudi Arabia. The problem arises when the Saudi government restructured the higher education system. As a result, new job requirements lower the level of satisfaction, organisational commitment and decrease the performance of academic staff. Data were collected from five public universities in the Kingdom using a cross-sectional study design. There were 384 respondents selected using cluster random sampling. The study used survey and the questionnaires were personally-administered. Partial Least Squares Structural Equation Modelling (PLS-SEM) was used to test the hypotheses in this study. The findings reveal that job performance depends on the degree of job satisfaction and employees’ empowerment. In contrast, the finding does not support the moderating effect of Islamic culture on the relationship between job satisfaction and job performance among the academicians. The results further show that organization commitment mediates between job satisfaction and job performance among the academicians. Furthermore, external job satisfaction does not have any significant influence on the job performance of the academicians. The results provide important insights to owners-managers, policy-makers and researchers to have a greater understanding on the effects of employee empowerment, job satisfaction and organizational commitment on organization performance. The policy makers of universities should emphasize on employees’ empowerment, job satisfaction and organizational commitment. It is also important to note that an over-concentration on Islamic culture may result in lower job performance. Policy-makers should encourage academicians to improve their organizational commitment and provide opportunities to the latter since employees’ empowerment encourages their job performance. Limitations of the present study and avenues for future research are also being discussed.